Ten ways to make the most of World Antimicrobial Awareness Week - Bradley J. Langford; Kelly L. Matson; Khalid Eljaaly; Anucha Apisarnthanarak; Pamela L. Bailey; Lindsay MacMurray; Alexandre R. Marra; Kari A. Simonsen; Pranavi Sreeramoju; Priya Nori; Gonzalo M. Bearman (Cambridge University Press, 2022)
One fundamental strategy to address the public health threat of antimicrobial resistance (AMR) is improved awareness among the public, prescribers, and policy makers with the aim of engaging these groups to act. World Antimicrobial Awareness Week is an opportunity for concerted and consistent communication regarding practical strategies to prevent and mitigate AMR. We highlight 10 ways for antimicrobial stewards to make the most of World Antimicrobial Awareness Week.